2010
DOI: 10.1108/01140581011034191
|View full text |Cite
|
Sign up to set email alerts
|

New Zealand unit trust disclosure: asset allocation, style analysis, and return attribution

Abstract: Purpose -This article aims to explore three facets of the historical performance of a sample of actively managed unit trusts available to New Zealand investors: asset allocation, style analysis, and return attribution. Design/methodology/approach -Because New Zealand does not require unit trusts to disclose their security holdings, the paper used returns-based style analysis to infer how these trusts have allocated their funds among asset classes. Findings -The research has found that, for unit trusts availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
(20 reference statements)
1
8
0
Order By: Relevance
“…In Australasia, Gallagher (2007) examines the case for requiring mandatory portfolio holdings disclosure in Australia in a qualitative study. This researcher also offers support for the case of mandatory disclosure of portfolio holdings, which is in line with Fowler et al (2010) and…”
Section: Australasia Researchsupporting
confidence: 62%
See 3 more Smart Citations
“…In Australasia, Gallagher (2007) examines the case for requiring mandatory portfolio holdings disclosure in Australia in a qualitative study. This researcher also offers support for the case of mandatory disclosure of portfolio holdings, which is in line with Fowler et al (2010) and…”
Section: Australasia Researchsupporting
confidence: 62%
“…Most researchers have determined that using aggregate portfolio data may disguise important information (Engstrom, 2004), and most recent studies focus on using portfolio holdings data to determine fund trading in order to more precisely measure fund skill (e.g., Comerton-Forde, Gallagher, Nahhas & Walter, 2010;Engstrom, 2004;Wermer, 2000). Fowler et al (2010) found that New Zealand active managers do not provide any excess returns, a significant finding for the industry. However, the viability of the conclusions is questioned due to the old-fashioned methods employed.…”
Section: Australasia Researchmentioning
confidence: 92%
See 2 more Smart Citations
“…Investors who need experts to invest on their behalf are generally unsophisticated; if they lack the knowledge or resources to evaluate an issuer they are unlikely to be competent to evaluate an intermediary such as a DIMS adviser (Bank of New Zealand, 2010). Recent studies have found evidence that New Zealand authorised advisers providing DIMS are deviating from their stated investment objectives, with equity-oriented funds providing returns that differ significantly from underlying equity returns (Fowler, Grieves, & Singleton, 2010). This further suggests that poor information about portfolio asset allocation limits opportunities for investors to diversify.…”
Section: Importance Of Product Disclosure Information To Retail Invesmentioning
confidence: 99%